Sex differences in features of atherosclerotic plaques as revealed by various imaging techniques: historical review - Laban, Dalya; Kattan, Alice; Ait-Abdellah, Lamia; Krishna, Hema; Le Master, Elizabeth; Levitan, Irena (Frontiers in Physiology, 2025)
Numerous studies over several decades found that there are significant sex differences in the development and severity of atherosclerosis, which include plaque burden, composition and vulnerability to rupture. This review provides historical analysis of these studies starting with early histological analysis of post mortem samples to modern high-resolution imaging techniques. It is discussed that the abundance of evidence obtained by an array of approaches demonstrates that men are more prone to develop atherosclerosis, which manifests itself in earlier initiation of the plaques, while the occurrence of plaque is accelerated following menopause. These findings unequivocally show that men are more likely to develop plaques with larger lipid-rich necrotic cores, thinner fibrous caps, and stronger inflammatory responses, resulting in increased vulnerability at a younger age. However, the rapid escalation of plaque instability in postmenopausal women, which is caused by a significant reduction in smooth muscle cell density and changes in calcification patterns, results in comparable atherosclerotic burden in men and women in older adults. These findings highlight how differences in sex and age, influence the development and severity of atherosclerosis. Understanding these differences is essential for creating better ways to assess and treat heart disease in men and women.